Regulating charitable organization in Malaysia with special references to waqaf corporation - Ali, Zuraidah; Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (2017)
Charities are noble act that are recommended in any aspect of life. A charitable organizations, which are dedicated for public purposes, have been used to channel the donor’s gift to the recipient and one of the way is through the charitable corporation. Waqf on the other hand is another form of charities, which in Malaysia comes under the purview of the states. This paper will analyze the working of corporate waqf in Malaysia, the differences with the present waqf management under SIRCs, together with advantages and disadvantages in its administration and implementation. This study employs a doctrinal approach of research methodology whereby it reviews the available literatures, the laws, and the policy in order to conclude as to whether there is a need to have a proper regulator in ensuring whether transparency and good governance has been carried upon this waqf corporations and ways for further improvements.